2021
DOI: 10.1177/00033197211005590
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impact of Ranolazine Treatment on Liver Function Tests in Patients With Coronary Heart Disease and Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common liver pathology in the developed world. Nonalcoholic fatty liver disease is associated with a higher risk of cardiovascular disease. We investigated the impact of ranolazine on liver tests in patients with NAFLD and coronary artery disease (CAD). Patients who had established CAD and NAFLD (as assessed by raised serum transaminase activity, sonographic criteria, and the absence of any other obvious liver disease) were allocated to “on ranolazine” (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 32 publications
(47 reference statements)
1
13
0
Order By: Relevance
“…In this context, statins are a favorable option possibly combined with ranolazine. Larger, randomized, placebo-controlled trials are needed to confirm the interesting preliminary findings reported by Esenboga et al 10 These findings may influence the choice of treatment for patients with angina and NAFLD.…”
mentioning
confidence: 76%
See 4 more Smart Citations
“…In this context, statins are a favorable option possibly combined with ranolazine. Larger, randomized, placebo-controlled trials are needed to confirm the interesting preliminary findings reported by Esenboga et al 10 These findings may influence the choice of treatment for patients with angina and NAFLD.…”
mentioning
confidence: 76%
“…Lipid levels, renal function tests, g-glutamyl transpeptidase activity, and albumin levels were not affected by the use of ranolazine. 10 This is the first study assessing the impact of ranolazine in patients with overt CV disease and NAFLD, and it showed potential benefits with ranolazine on liver tests. 10 However, to establish any potential benefits of ranolazine (or any drug) on NAFLD, the use of liver biopsy to identify relevant ameliorating effects is necessary, since this is considered as the gold standard for the diagnosis of NAFLD and NASH.…”
mentioning
confidence: 85%
See 3 more Smart Citations